Steel plates, components and their manufacturing methods
Patent Information
- Application Number
- JP2024542202
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-14
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2044-03-14
Smart Images

Figure 0007635895000012 
Figure 0007635895000013 
Figure 0007635895000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength steel plate and member having excellent formability and used in various applications such as automobiles and home appliances, and particularly suitable for energy absorbing members, and to a manufacturing method thereof. [Background technology]
[0002] In recent years, the need for lighter automobile bodies has increased, and high-strength steel sheets with a tensile strength (TS) of 980 MPa or more are increasingly being used for automobile frame parts and seat parts. However, when these high-strength steel sheets are formed by cold pressing, press cracks tend to occur due to reduced ductility and stretch flangeability. For this reason, these high-strength steel sheets are required to have better formability than conventional steel sheets.
[0003] In addition, to ensure passenger safety, it is necessary to suppress deformation around the cabin during a collision, so energy absorbing components such as side members are required to absorb collision energy by deforming during a collision. However, with high-strength steel plates with a tensile strength of 980 MPa or more, due to reduced axial crush properties, components are likely to break at the points that have been subjected to primary processing by forming during a collision, and there is an issue that they cannot stably absorb collision energy.
[0004] For the above reasons, in order to apply high-strength steel sheets of 980 MPa or more to energy absorbing components of automobiles, they are required to have excellent axial crush properties in addition to ductility and stretch flangeability.
[0005] In this context, for example, Patent Document 1 describes the following, in mass %, C: 0.15% or more and 0.30% or less, P: 0.040% or less, S: 0.0100% or less, N: 0.0100% or less, O: 0.0060% or less, one or two of Si and Al: 0.70% or more and 2.50% or less in total, one or two of Mn and Cr: 1.50% or more and 3.50% or less in total. %, Mo: 0% or more, 1.00% or less, Ni: 0% or more, 1.00% or less, Cu: 0% or more, 1.00% or less, Nb: 0% or more, 0.30% or less, Ti: 0% or more, 0.30% or less, V: 0% or more, 0.30% or less, B: 0% or more, 0.0050% or less, Ca: 0% or more, 0.0400% or less, Mg: 0% or more, 0.0400% or less, and REM It is disclosed that the steel sheet contains 0% or more and 0.0400% or less, with the balance consisting of Fe and impurities, and the area ratio relative to the entire structure is as follows: one or two of ferrite and granular bainite: 10% or more and 50% or less in total, one or two of upper bainite and lower bainite: 10% or more and 50% or less in total, tempered martensite: more than 0% and 30% or less, retained austenite: 5% or more, and one or two or more of pearlite, cementite, and martensite: 0% or more and 10% or less in total, and by setting the area ratio of the ferrite to the total area ratio of the ferrite and the granular bainite to 25% or less, a steel sheet having a tensile strength of 980 MPa or more and excellent elongation and hole expandability can be obtained.
[0006] In Patent Document 2, the steel composition contains, by mass%, C: 0.07 to 0.20%, Si: 0.1 to 2.0%, Mn: 2.0 to 3.5%, P: 0.05% or less, S: 0.05% or less, and Sol.Al: 0.005 to 0.1%, with the balance being Fe and unavoidable impurities. The steel structure contains, by area ratio, ferrite: 60% or less, tempered martensite: 40% or more, and fresh martensite: 10% or less. In addition, the void number density of the bent part in the VDA bending test is 1500 voids / mm 2 It is disclosed that by satisfying the following conditions, a high-strength hot-dip galvanized steel sheet having a tensile strength of 980 MPa or more and excellent fracture resistance in the event of a collision can be obtained.
[0007] Patent Document 3 discloses that a high-strength cold-rolled steel sheet excellent in strength, ductility, and hole expandability can be obtained by containing, by mass%, C: 0.10 to 0.40%, Mn: 0.5 to 4.0%, Si: 0.005 to 2.5%, Al: 0.005 to 2.5%, Cr: 0 to 1.0%, with the balance being iron and unavoidable impurities, with P: limited to 0.05% or less, S: limited to 0.02% or less, and N: limited to 0.006% or less, with the steel structure containing, by area ratio, 2 to 30% retained austenite and limited to 20% martensite, with the average grain size of cementite being 0.01 μm or more and 1 μm or less, and the cementite containing 30% or more and 100% or less of cementite having an aspect ratio of 1 or more and 3 or less. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 6338038 [Patent Document 2] Patent No. 6795122 [Patent Document 3] Patent No. 4903915 Publication Summary of the Invention [Problem to be solved by the invention]
[0009] However, while the techniques described in Patent Documents 1 and 3 provide high-strength steel sheets excellent in ductility and stretch flangeability, they do not take into consideration axial crush properties.
[0010] Furthermore, Patent Document 2 discloses that high-strength steel sheets of 980 MPa or more have excellent fracture resistance properties during collision, but does not consider formability and is limited to steel sheets having a hot-dip galvanized layer.
[0011] The present invention has been made to solve the above-mentioned problems, and has an object to provide a steel plate, a member, and a manufacturing method thereof, which have a tensile strength (TS) of 980 MPa or more, high ductility and stretch flangeability, and excellent axial crush characteristics.
[0012] In the present invention, the tensile strength is measured by a tensile test in accordance with JIS Z 2241 (2011).
[0013] In the present invention, high ductility means that the total elongation (T-El) measured in a tensile test according to JIS Z 2241 (2011) is: (A) When TS is in the range of 980 MPa or more and less than 1180 MPa, T-El is 14.0% or more; (B) When TS is in the range of 1180 MPa or more and less than 1320 MPa, T-El is 12.0% or more; (C) This indicates that when TS is in the range of 1,320 MPa or more, T-El is 10.0% or more.
[0014] In the present invention, high stretch flangeability refers to a hole expansion ratio λ(%)={(d-d0) / d0}×100 of 45% or more, in which a sample of 100 mm×100 mm square size is punched using a punching tool with a punch diameter of 10 mm and a die diameter of 10.3 mm (clearance 13%), and then the hole is expanded using a conical punch with an apex angle of 60 degrees so that burrs generated during the formation of the punched hole are on the outside until a crack penetrating the plate thickness occurs, where d0 is the initial hole diameter (mm) and d is the hole diameter (mm) when the crack occurs.
[0015] In the present invention, excellent axial crushing properties refers to a steel sheet having a VDA bending angle α of 80° or more in VDA bending.
[0016] Here, the VDA bending test refers to a bending test (Verband der Automobilindustrie: VDA bending test) in accordance with the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry, and is a three-point plate bending test characterized by very narrowly spaced rolls and a sharp punch. The VDA bending test uses a 60 mm x 60 mm square test piece, supports the bending ridge direction parallel to the rolling direction with roll diameter D of 30 mm and roll distance L of (plate thickness a0 x 2) + 0.5 mm, and is performed by pressing from above with a punch with a tip r of 0.4 mm at a stroke speed of 20 mm / min. The VDA bending angle α is the bending angle (° (more specifically, the unit is "° / mm", but hereinafter it is expressed as "°")) calculated using the formulas (1) to (5) from the stroke S (mm) at the maximum load in the bending test, and can be used as an index of axial crushing properties. The stroke S (mm) at the maximum load is the length (mm) that the punch moves from the start of the test to the point at which the maximum load is obtained.
[0017] c(mm)=D / 2+r+a0...(Formula 1)
[0018] p(mm)=D / 2+L / 2 (Equation 2)
[0019]
number
[0020]
number
[0021]
number
[0022] The present inventors have conducted extensive research into a steel plate having high strength, excellent ductility and stretch flangeability, and further excellent axial crush resistance, and have reached the following conclusions. (1) After hot rolling and cold rolling a steel slab having a predetermined composition, the annealing temperature: (A c3 Annealing is performed in the austenite single phase region of temperature (℃) -15℃ or higher and 900℃ or lower, and cooling is performed at a prescribed cooling rate from the annealing temperature to control the area ratio of ferrite to 15% or less. (2) In the cooling process after the above annealing treatment, the cooling stop temperature is set to 200°C or higher and (the martensitic transformation start temperature Ms point (°C) - 30°C) or lower, thereby partially replacing austenite with martensite and / or bainite. The martensite and bainite thus produced enrich carbon in the surrounding untransformed austenite during the overaging process after cooling is stopped, ensuring a specified C concentration in the retained austenite and contributing to improved ductility. In addition, a retention treatment can be performed during cooling, and by retaining the material in a temperature range from 500°C to the martensitic transformation start temperature Ms point and 320°C or higher for 10 to 60 seconds, more bainite can be obtained and further ductility can be improved. (3) In the above-mentioned overaging treatment process after cooling is stopped, the steel sheet is heated to a heating temperature of 300°C to 450°C. Next, the steel sheet is cooled at an average cooling rate of 0.5°C / s or more to a temperature 30°C to 150°C lower than the above-mentioned heating temperature, and further cooled at an average cooling rate of 0.1°C / s or more to a temperature of 150°C to 350°C. Next, the steel sheet is held at a temperature range of 150°C to 350°C for 20 s to 1000 s. This makes it possible to minimize the precipitation of carbides in the tempered martensite present in the surface layer of the steel sheet, which is the starting point for crack propagation during VDA bending, and improve the axial crushing properties. In addition, the above-mentioned heat treatment process (heating to 300 to 450°C after cooling is stopped, and then finally holding the temperature in the range of 150°C to 350°C for 20 s to 1,000 s) promotes carbon distribution from the surrounding structure to the untransformed austenite region, thereby making it possible to further increase the carbon concentration of the retained austenite and improve ductility.
[0023] In this way, by appropriately controlling the temperature history, particularly during the cooling process after annealing and the overaging process, it is possible to simultaneously reduce the amount of carbides in the tempered martensite and increase the carbon concentration of the retained austenite. As a result, it is possible to manufacture steel sheets that have a tensile strength (TS) of 980 MPa or more, as well as excellent ductility, stretch flangeability, and axial crush resistance.
[0024] The present invention has been made based on the above findings, and specifically provides the following. [1] In mass percent, C: 0.10% or more and 0.30% or less, Si: 0.5% or more and 2.0% or less, Mn: 1.5% or more and 3.0% or less, P: 0.10% or less, S: 0.020% or less, Sol.Al: 1.00% or less, N: 0.015% or less The composition is composed of the remainder Fe and unavoidable impurities, In terms of area ratio, Ferrite: 15% or less, Tempered martensite: 30% to 80% Bainite: 10% to 40% Retained austenite: 5% or more, Fresh martensite: 10% or less The steel structure contains The average C concentration in the retained austenite is 0.60 mass% or more, A steel sheet in which the content of Fe element present as carbides in tempered martensite is 0.20 mass% or less on average in a region within 100 μm from the steel sheet surface in the sheet thickness direction. [2] The composition further includes, in mass%, Ti: 0.100% or less, Nb: 0.100% or less, V: 0.100% or less, B: 0.0050% or less, Cr: 1.000% or less, Cu: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.100% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, REM: 0.0050% or less The steel sheet according to the above [1], comprising at least one selected from the following: [3] The steel sheet according to [1] or [2] above, having a zinc-plated layer on the surface of the steel sheet. [4] A member made using the steel plate according to any one of [1] to [3] above. [5] A steel slab having the composition described in [1] or [2] above is hot-rolled and cold-rolled, and then the resulting cold-rolled steel sheet is subjected to (A c3 After annealing at an annealing temperature of 900°C or higher (temperature (℃) -15°C), Cooling is performed at an average cooling rate CR1 of 3°C / s or more and 100°C / s or less in the range from the annealing temperature to a temperature T1 of 200°C or more and (Ms point (°C) - 30°C) or less, Heating the temperature range from the temperature T1 to a temperature T2 of 300° C. or more and 450° C. or less at an average heating rate of 2° C. / s or more; Cooling the temperature range from the temperature T2 to a temperature T3 of (T2-150°C) or more and (T2-30°C) or less at an average cooling rate CR2: 0.5°C / s or more; Cooling the material at an average cooling rate CR3 of 0.1° C. / s or more in a temperature range from the temperature T3 to a temperature T4 of 150° C. or more and 350° C. or less and equal to or less than the temperature T3; Maintaining the temperature range of 150°C to 350°C and the temperature T4 or less for 20s to 1000s, A manufacturing method for steel plate in which the steel is cooled to a temperature of 50°C or less at an average cooling rate of CR4:1°C / s or more. [6] A steel slab having the composition described in [1] or [2] above is hot-rolled and cold-rolled, and then the resulting cold-rolled steel sheet is subjected to (A c3 After annealing at an annealing temperature of 900°C or higher (temperature (℃) -15°C), Cooling the steel sheet from the annealing temperature to 500°C at an average cooling rate of CR5: 5°C / s or more and 100°C / s or less; The temperature range is from 500°C to the retention stop temperature T5, which is above the Ms point (°C) and above 320°C, and the retention time is 10 seconds or more and 60 seconds or less at an average cooling rate of CR6: 10°C / s or less. Cooling the temperature range from the retention end temperature T5 to a temperature T1 of 200°C or more and (Ms point (°C) - 30°C) or less at an average cooling rate CR7: 3°C / s or more and 100°C / s or less; Heating the temperature range from the temperature T1 to a temperature T2 of 300° C. or more and 450° C. or less at an average heating rate of 2° C. / s or more; Cooling the temperature range from the temperature T2 to a temperature T3 of (T2-150°C) or more and (T2-30°C) or less at an average cooling rate CR2: 0.5°C / s or more; Cooling the material at an average cooling rate CR3 of 0.1° C. / s or more in a temperature range from the temperature T3 to a temperature T4 of 150° C. or more and 350° C. or less and equal to or less than the temperature T3; Maintaining the temperature range of 150°C to 350°C and the temperature T4 or less for 20s to 1000s, A manufacturing method for steel plate in which the steel is cooled to a temperature of 50°C or less at an average cooling rate of CR4:1°C / s or more. [7] The method for producing a steel sheet according to [5] above, further comprising the steps of: cooling the steel sheet at an average cooling rate CR1 of 3°C / s or more and 100°C / s or less, followed by hot-dip galvanizing or hot-dip galvannealing treatment. [8] The method for producing a steel sheet according to [6] above, further comprising the steps of: cooling the steel sheet at an average cooling rate CR7 of 3°C / s or more and 100°C / s or less, followed by hot-dip galvanizing or hot-dip galvannealing treatment. [9] The method for producing a steel sheet according to [5] or [6], further comprising the steps of: cooling the steel sheet at an average cooling rate of CR4:1°C / s or more, and then subjecting the steel sheet to an electrolytic galvanizing treatment.
[10] A method for producing a component, comprising the step of subjecting the steel plate according to any one of [1] to [3] above to at least one of forming and joining to produce a component. Effect of the Invention
[0025] According to the present invention, it is possible to obtain a steel sheet having a tensile strength (TS) of 980 MPa or more and excellent ductility, stretch flangeability and axial crush resistance. The steel plate of the present invention has excellent axial crushing properties and is therefore suitable for energy absorbing members. By applying the steel sheet obtained according to the present invention to automobile parts, a reduction in vehicle weight can be realized, and improvement in fuel efficiency is expected. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a photograph of the structure of an example of the steel sheet of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a method for measuring the steel structure of the steel plate of the present invention. [Diagram 3] FIG. 3 is a diagram for explaining the method for producing a steel sheet according to the present invention. [Figure 4] FIG. 4 is a diagram for explaining a method for calculating the VDA bending angle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will be specifically described below. The steel sheet of the present invention has a composition, by mass%, of C: 0.10% or more and 0.30% or less, Si: 0.5% or more and 2.0% or less, Mn: 1.5% or more and 3.0% or less, P: 0.10% or less, S: 0.020% or less, sol.Al: 1.00% or less, N: 0.015% or less, with the balance being Fe and unavoidable impurities, and has a steel structure containing, by area ratio, ferrite: 15% or less, tempered martensite: 30% or more and 80% or less, bainite: 10% or more and 40% or less, retained austenite: 5% or more, and fresh martensite: 10% or less, the average C concentration in the retained austenite is 0.60 mass% or more, and the content of Fe element present as carbide in the tempered martensite is 0.20 mass% or less on average in a region within 100 μm from the steel sheet surface in the sheet thickness direction.
[0028] First, the chemical composition of the steel sheet of the present invention will be described. In the following description, the unit of content of each component element, "%", means "mass%" unless otherwise specified.
[0029] [C: 0.10% or more and 0.30% or less] C is essential for securing the amount of tempered martensite and the amount of retained austenite stable at room temperature, and is also an element necessary for stabilizing the retained austenite by concentrating it in the retained austenite and improving ductility. If the C content is less than 0.10%, these effects cannot be fully exerted, and it becomes difficult to secure the strength and workability of the steel sheet. Therefore, the C content must be 0.10% or more, preferably 0.12% or more, and more preferably 0.15% or more. On the other hand, if the C content exceeds 0.30%, the amount of carbides in the tempered martensite increases, and cracks are generated from the carbides during bending deformation, which deteriorates the axial crushing properties and reduces the ductility due to the excessive increase in strength. Therefore, the C content must be 0.30% or less, preferably 0.28% or less, and more preferably 0.25% or less.
[0030] [Si: 0.5% or more and 2.0% or less] Silicon is an element that is useful for suppressing the formation of carbides in martensite and bainite, promoting the formation of retained austenite, and improving the stability of the retained austenite. To obtain these effects, the silicon content must be 0.5% or more, preferably 0.6% or more, and more preferably 0.7% or more. On the other hand, if the Si content exceeds 2.0%, excessive strength is increased, which leads to a decrease in ductility and stretch flangeability, and there are concerns about an increase in rolling load during hot rolling, liquid metal embrittlement cracking when welded to a galvanized material, and a decrease in chemical conversion treatability. Therefore, the Si content is set to 2.0% or less, preferably 1.5% or less, and more preferably 1.0% or less.
[0031] [Mn:1.5% or more and 3.0% or less] Mn is effective in ensuring a certain area ratio of tempered martensite and / or bainite to ensure strength. It is also an important element for increasing the area ratio of retained austenite and improving ductility by stabilizing the retained austenite by lowering the Ms point of the retained austenite. Therefore, the Mn content must be 1.5% or more, preferably 1.8% or more, and more preferably 2.0% or more. On the other hand, if the Mn content exceeds 3.0%, not only will the strength be excessively high, but the bainite transformation will be significantly delayed, resulting in a decrease in ductility. Also, Mn segregation in the thickness direction will be significant, raising concerns about a decrease in material stability. Therefore, the Mn content is set to 3.0% or less, preferably 2.8% or less, and more preferably 2.5% or less.
[0032] [P:0.10% or less] P is an element that strengthens steel, but if the content is high, it deteriorates spot weldability. Therefore, the P content is set to 0.10% or less, and preferably 0.02% or less. Note that P may not be contained, but the P content is preferably 0.001% or more from the viewpoint of manufacturing costs.
[0033] [S:0.020% or less] S has the effect of improving scale peeling during hot rolling and the effect of suppressing nitriding during annealing, but is an element that has a large adverse effect on bendability, hole expandability, and spot weldability. In order to reduce these adverse effects, the S content is at least 0.020% or less. In the present invention, from the viewpoint of suppressing the deterioration of bendability and hole expandability, the S content is preferably 0.0020% or less, and more preferably less than 0.0010%. Although S may not be contained, the S content is preferably 0.0001% or more from the viewpoint of manufacturing costs. The S content is more preferably 0.0005% or more.
[0034] [sol.Al: 1.00% or less] Al is an element that is effective in suppressing the formation of carbides and promoting the formation of retained austenite. It is also an element that is added as a deoxidizer in the steelmaking process. Therefore, although there is no particular lower limit for the sol.Al content, it is preferably 0.005% or more, and more preferably 0.01% or more, in order to perform stable deoxidation. On the other hand, if the sol.Al content exceeds 1.00%, the number of inclusions in the steel sheet increases, deteriorating ductility. Therefore, the sol.Al content is set to 1.00% or less, preferably 0.50% or less. The sol.Al content is more preferably 0.25% or less, and further preferably 0.10% or less.
[0035] [N:0.015% or less] N is an element that forms nitrides such as BN, AlN, and TiN in steel, and reduces the hot ductility of steel and the surface quality. In addition, in steel containing B, there is a drawback in that the effect of B is lost through the formation of BN. If the N content exceeds 0.015%, the surface quality is significantly deteriorated. Therefore, the N content is set to 0.015% or less, and preferably 0.010% or less. The N content is more preferably 0.005% or less, and further preferably 0.002% or less. Although N does not necessarily have to be contained, the N content is preferably 0.0001% or more from the viewpoint of production costs, and more preferably 0.001% or more.
[0036] The balance other than the above is Fe and unavoidable impurities. The steel sheet of the present invention preferably has a composition containing the above basic components, with the balance being iron (Fe) and unavoidable impurities.
[0037] The composition of the steel sheet of the present invention may contain the following optional elements as appropriate in addition to the above-mentioned components.
[0038] [Ti: 0.100% or less, Nb: 0.100% or less, V: 0.100% or less] Ti, Nb and V form fine precipitates during hot rolling or annealing to increase strength. To obtain such effects, it is preferable that Ti is 0.010% or more, Nb is 0.020% or more, and V is 0.020% or more. On the other hand, when the content of Ti, Nb and V exceeds 0.100%, the formability is deteriorated. Therefore, when Ti, Nb and V are added, the content of each is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.050% or less.
[0039] [B:0.0050% or less] B is an element that improves the hardenability of steel and has the advantage of easily forming a predetermined area ratio of tempered martensite and / or bainite. To obtain such an effect, B is preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the content of B exceeds 0.0050%, not only does the effect saturate, but also the hot ductility is significantly reduced and surface defects are generated. Therefore, when B is added, the content of B is preferably 0.0050% or less, more preferably 0.0040% or less, and further preferably 0.0025% or less.
[0040] [Cr: 1.000% or less, Cu: 1.000% or less] Cr and Cu not only play a role as solid solution strengthening elements, but also stabilize austenite and facilitate the formation of a composite structure during the cooling process during annealing. Therefore, although it is not necessary to include Cr and Cu, in order to obtain such effects, the contents of Cr and Cu are preferably 0.005% or more, more preferably 0.008% or more, and further preferably 0.010% or more, respectively. The Cr and Cu contents are each preferably 0.020% or more, and more preferably 0.04% or more. On the other hand, if the Cr content or Cu content exceeds 1.000%, the formability of the steel sheet decreases. Therefore, when Cr and Cu are added, their contents are preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.400% or less. The Cr and Cu contents are preferably 0.200% or less, and more preferably 0.100% or less.
[0041] [Sb: 0.200% or less, Sn: 0.200% or less] Sb and Sn are elements effective in suppressing decarburization in a region of about several tens of μm in the surface layer of the steel sheet caused by nitriding and oxidation of the steel sheet surface. Suppressing such nitriding and oxidation prevents a decrease in the amount of martensite formed on the steel sheet surface, making it possible to ensure the strength and material stability of the steel sheet. Therefore, it is not necessary to add Sb and Sn, but if added, the contents of Sb and Sn are preferably 0.002% or more, more preferably 0.004% or more, and even more preferably 0.006% or more. On the other hand, excessive content of any of these elements exceeding 0.200% leads to a decrease in toughness. Therefore, when Sb and Sn are added, the Sb and Sn contents are preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.040% or less.
[0042] [Ta:0.100% or less] Ta, like Ti and Nb, forms alloy carbides and alloy carbonitrides, contributing to high strength. In addition, it is considered to have the effect of partially dissolving in Nb carbides and Nb carbonitrides, forming composite precipitates such as (Nb,Ta)(C,N), significantly suppressing the coarsening of precipitates, and stabilizing the contribution rate to the strength improvement of steel sheets by precipitation strengthening. To obtain such effects, Ta is preferably 0.005% or more. On the other hand, if Ta is added in excess, the precipitate stabilizing effect becomes saturated and the alloy cost increases, so when Ta is added, the Ta content is preferably 0.100% or less, more preferably 0.080% or less, and further preferably 0.050% or less.
[0043] [Ca: 0.0050% or less, Mg: 0.0050% or less, REM: 0.0050% or less] Ca, Mg and REM are elements used for deoxidization, and are also effective in spheroidizing the shape of sulfides and improving the adverse effects of sulfides on local ductility and stretch flangeability. To obtain such effects, it is preferable that the Ca content is 0.0001% or more, the Mg content is 0.0001% or more, and the REM content is 0.0001% or more. On the other hand, when the content of Ca, Mg and REM exceeds 0.0050%, it causes an increase in inclusions and the like, which leads to defects on the surface and inside. Therefore, the content of Ca, Mg and REM is preferably 0.0050% or less, more preferably 0.0025% or less, and further preferably 0.0010% or less. The Ca content is more preferably 0.0008% or less. The Mg content is more preferably 0.0008% or less. The REM content is more preferably 0.0008% or less.
[0044] In the present invention, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM content in the present invention is the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably La and / or Ce.
[0045] When the optional elements are contained in an amount less than the preferred lower limit, the optional elements contained in an amount less than the preferred lower limit do not impair the effects of the present invention.When the optional elements are contained in an amount less than the preferred lower limit, the optional elements are considered to be contained as unavoidable impurities.
[0046] Next, the steel structure (microstructure) of the steel plate of the present invention will be described.
[0047] [Ferrite area ratio: 15% or less] Ferrite formed during annealing or cooling contributes to improving ductility, but it causes a difference in hardness with the surrounding hard phases such as martensite, and cracks develop from the interface between the ferrite and the hard phase during bending, resulting in a decrease in stretch flangeability and axial crushing properties. If the area ratio of ferrite is 15% or less, the effect of the present invention is not impaired, so it is set to 15% or less. The area ratio of ferrite is preferably 10% or less, and more preferably 5% or less. Ferrite may also be 0%.
[0048] [Area ratio of tempered martensite: 30% to 80%] In order to obtain a desired strength and stretch flangeability, the area ratio of tempered martensite is set to 30% or more, preferably 40% or more, and more preferably 50% or more. On the other hand, if the area ratio of tempered martensite exceeds 80%, ductility decreases due to excessively high strength, so the area ratio of tempered martensite is set to 80% or less, preferably 75% or less, and more preferably 70% or less.
[0049] [Bainite: 10% to 40%] In the present invention, bainite is a general term for upper bainite and lower bainite. Here, upper bainite and lower bainite are defined as follows. Upper bainite is composed of lath-shaped bainitic ferrite and retained austenite and / or carbides present between the bainitic ferrite, and is characterized by the absence of regularly arranged fine carbides in the lath-shaped bainitic ferrite. On the other hand, lower bainite is similar to upper bainite in that it is composed of lath-shaped bainitic ferrite and retained austenite and / or carbides present between the bainitic ferrite, but lower bainite is characterized by the presence of regularly arranged fine carbides in the lath-shaped bainitic ferrite. That is, upper bainite and lower bainite are distinguished by the presence or absence of regularly arranged fine carbides in the bainitic ferrite. Bainite, which is formed during the cooling process after annealing and during the retention process during the cooling process, concentrates carbon in the surrounding untransformed austenite regions, making it possible to efficiently obtain more stable retained austenite. Therefore, the area ratio of bainite is set to 10% or more. On the other hand, since bainite is softer than tempered martensite, excessive formation of bainite leads to a decrease in strength and a decrease in stretch flangeability due to an increase in the difference in hardness with tempered martensite. Therefore, the area fraction of bainite is set to 40% or less, preferably 35% or less, and more preferably 30% or less. In addition, since upper bainite concentrates more carbon in the surrounding untransformed austenite region than lower bainite, upper bainite is advantageous from the viewpoint of efficiently obtaining retained austenite. Therefore, it is preferable that the upper bainite content is 10% or more, and more preferably 15% or more. On the other hand, since upper bainite is softer than lower bainite, excessive generation of upper bainite is disadvantageous from the viewpoint of improving strength and stretch flangeability. Therefore, upper bainite is preferably 30% or less, more preferably 25% or less.
[0050] [Area ratio of retained austenite: 5% or more] In order to obtain a desired strength while ensuring high ductility, the area fraction of retained austenite in the entire steel structure is set to 5% or more, preferably 7% or more, and more preferably 10% or more. The amount of retained austenite includes the retained austenite present between the bainitic ferrite particles. The area ratio of the retained austenite present between the bainitic ferrite particles can be measured in the same manner as the area ratios of the other retained austenite particles, by the measurement method described later. On the other hand, if the amount of retained austenite is too large, it may lead to a decrease in strength, a decrease in stretch flange formability, and a deterioration in delayed fracture resistance. Therefore, although there is no upper limit for the area ratio of retained austenite, the area ratio of retained austenite is preferably 20% or less, and more preferably 15% or less.
[0051] [Area ratio of fresh martensite: 10% or less] Since this may result in a decrease in ductility and stretch flangeability, the area ratio of fresh martensite is set to 10% or less, preferably 8% or less, and more preferably 5% or less. Also, the area ratio of fresh martensite may be 0%.
[0052] [Average C concentration in retained austenite: 0.60 mass% or more] By increasing the C concentration in the retained austenite, the retained austenite is stabilized and ductility can be improved. Therefore, in order to obtain sufficient ductility while ensuring the desired strength, the average C concentration in the retained austenite is set to 0.60 mass% or more, and preferably 0.80 mass% or more. Although there is no particular upper limit, if the average C concentration in the retained austenite increases excessively, the retained austenite may not transform during deformation, and the effect of improving ductility may not be sufficiently obtained. Therefore, the average C concentration in the retained austenite is preferably 2.0 mass% or less, and more preferably 1.5 mass% or less.
[0053] [Fe content present as carbides in tempered martensite within 100 μm from the steel plate surface in the plate thickness direction: 0.20 mass% or less on average] Carbide precipitated in tempered martensite becomes the starting point of cracks during bending deformation, leading to a decrease in axial crushing properties. In addition, carbide precipitation is a phenomenon that competes with carbon distribution, and there is a concern that carbon consumption in the carbide precipitation may inhibit carbon concentration in untransformed austenite. Therefore, the content of Fe element present as carbide in tempered martensite is preferably 0.20 mass% or less on average, more preferably 0.15 mass% or less. Although there is no particular lower limit, in the present invention, the content of the Fe element is substantially 0.001 mass% or more.
[0054] As described above, the steel structure of the present invention is a steel structure containing ferrite (including 0%), tempered martensite, bainite, retained austenite, and fresh martensite (including 0%). The steel structure of the present invention may be a steel structure consisting of ferrite (including 0%), tempered martensite, bainite, retained austenite, and fresh martensite (including 0%). Furthermore, the steel structure of the present invention may contain up to 5% of pearlite and cementite as phases other than those mentioned above, and these do not impair the effects of the present invention.
[0055] Next, a method for measuring the steel structure will be described.
[0056] The area ratio of the block structure consisting of ferrite, tempered martensite, fresh martensite and / or retained austenite (Martensite Austenite Constituent: MA), which will be described later, is measured by cutting out a cross section of the sheet thickness perpendicular to the steel sheet surface and parallel to the rolling direction, mirror polishing it, etching it with 3 vol% nital, and observing it at a position 1 / 4 of the sheet thickness with a magnification of 5000 times using an SEM with a field of view of 20 μm × 20 μm, and observing 10 fields of view. Figure 1 shows an example of an SEM photograph of the steel structure of a steel plate. As shown in Figure 1, ferrite (see symbol F in Figure 1) is the region that appears blackest in the SEM, with almost no carbides inside and is relatively equiaxed. Tempered martensite (see symbol TM in Figure 1) is the region that appears with lath-shaped substructure and carbide precipitation inside in the SEM. MA (fresh martensite and / or retained austenite) (see symbols FM and RA in Figure 1) is the lumpy region that appears white in the SEM, with no substructure visible inside.
[0057] In the present invention, bainite is defined as the sum of the area ratios of upper bainite and lower bainite. Upper bainite is determined by observation with an SEM in the same way as the above-mentioned ferrite. Upper bainite is a structure consisting of bainitic ferrite, which is the area that does not involve the precipitation of fine carbides arranged in a regular pattern and appears blackest on an SEM, and carbides or retained austenite that appear white on an SEM (see the symbol UB in Figure 1). When it is difficult to distinguish between ferrite and bainitic ferrite, the region of ferrite having an aspect ratio of ≦2.0 is defined as ferrite, and the region of ferrite having an aspect ratio of >2.0 is defined as bainitic ferrite. FIG. 2 is a diagram for explaining a method for measuring the steel structure of the steel plate of the present invention. As shown in FIG. 2, the aspect ratio is calculated as a / b regardless of whether the shape is an ellipse as shown in (1) or a polygon as shown in (2). Here, a refers to the longest line segment length among the line segments formed by two points on the outer periphery of the region of each phase, and b refers to the longest line segment length among the line segments formed by two points on the outer periphery of the region that is perpendicular to the straight line forming a. In addition, as shown in FIG. 2 (3), when calculating the aspect ratio, if grains are in contact with each other, they are not considered as one grain, but are measured by dividing them into two or more grains. Specifically, when particles are in contact with each other, as shown by the dashed line in Figure 2 (3), the particle size is measured by dividing the particle at a position where the area ratio of each particle is approximately equal. In addition, in SEM observation, both lower bainite (see symbol LB in Figure 1) and tempered martensite exhibit a structure in which fine white carbides are precipitated in a gray matrix, making it difficult to distinguish between them. Therefore, lower bainite and tempered martensite are distinguished by observing the variant morphology of the carbides using a TEM (Transmission Electron Microscopy). The carbide morphology of lower bainite is a single variant that is regularly precipitated in one direction within the substructure, whereas the carbides of tempered martensite are multi-variant with random precipitation directions within the substructure. The area ratios of lower bainite and tempered martensite, which show these characteristics, can be obtained by observing 10 fields of view in an area of 1.5 μm square using a TEM, calculating the area ratios of the constituent phases (lower bainite and tempered martensite) for the obtained structure images using the Adobe Photoshop, and averaging these values.
[0058] The area ratio of the retained austenite and the average C concentration in the retained austenite are determined by grinding and polishing the steel plate in the plate thickness direction to the 1 / 4 position and measuring the X-ray diffraction intensity. The volume ratio of the retained austenite is calculated from the intensity ratio of the (200), (220), and (311) planes of the austenite to the diffraction intensity of the (200) and (211) planes of the ferrite using a Mo tube radiation source. The average C concentration in the retained austenite is calculated from the lattice constant A of the austenite from the peak angle of the (220) plane of the austenite using a Co tube radiation source, and then calculated from the following formula (6). Note that Mn%, Si%, and Al% in the following represent the mass% content of each element (Mn, Si, Al) in the steel plate.
[0059] Average C concentration in retained austenite (mass%) = A - {(0.3572 + 0.0012 × Mn% - 00157 × Si% + 0.0056 × Al%)} / 0.033 (Equation 6)
[0060] The area fraction of fresh martensite (Fresh Martensite: FM) is calculated by the following formula (7) and is the value obtained by subtracting the area fraction of retained austenite (Retained Austenite: RA) from the area fraction of MA (fresh martensite and / or retained austenite). In the present invention, the "area fraction" of RA (retained austenite) can be considered to be equal to the "volume fraction" of retained austenite determined by XRD measurement.
[0061] FM(%)=MA(%)-RA(%) (Formula 7)
[0062] The average content of Fe present as carbides in tempered martensite in a region within 100 μm from the steel sheet surface in the sheet thickness direction is determined by extraction residue analysis. A 10 mass% AA electrolyte (acetylacetone-1 mass% tetramethylammonium chloride-methanol) was used as the electrolyte, and the current density was 20 mA / cm 2 Electrolysis is performed under the conditions of 100 μm from the surface of the steel sheet, and the electrolysis time is 30 min, dissolving the area up to 100 μm from the surface of the steel sheet. After that, the sample is immersed in methanol, and the residue (precipitates that remain after electrolysis) peeled off by ultrasonic stirring is filtered using a filter with a pore size of 0.2 μm, and the amount of Fe element in the collected residue is determined by ICP emission spectrometry and converted into mass % in the steel sheet. Note that the collected residue is all composed of precipitates present in the area within 100 μm from the surface of the steel sheet, and in this case, the amount of carbides outside the tempered martensite (bainite, ferrite, etc.) is extremely small compared to the amount of carbides in the tempered martensite. In addition, the Fe element is not present as an iron-based compound other than carbon-based. Therefore, the above measurement can obtain the average content of Fe element present as carbides in the tempered martensite in the area within 100 μm from the surface of the steel sheet in the sheet thickness direction.
[0063] The above-mentioned steel sheet of the present invention may be a steel sheet having a zinc plating layer on one or both sides of the steel sheet surface. The plating layer may be either a hot-dip plating layer or an electroplating layer.
[0064] The steel plate of the present invention preferably has a thickness of 0.5 mm or more, and more preferably has a thickness of 2.0 mm or less.
[0065] Next, a method for producing a steel sheet according to the present invention will be described. In the following, a case in which retention treatment under specified conditions is not performed as a subsequent treatment after annealing treatment will be described as a first embodiment, and a case in which retention treatment under specified conditions is performed as a subsequent treatment after annealing treatment will be described as a second embodiment.
[0066] In the present invention, the temperature specified in each step refers to the surface temperature of the slab (steel slab) or steel plate.
[0067] FIG. 3 is a diagram for explaining the steel sheet manufacturing method of the present invention, and in particular shows the change in surface temperature of a slab (steel slab) or a steel sheet over time. Details of each step, including the change in temperature over time, are described below. FIG. 3(a) shows the change in surface temperature of a slab (steel slab) or a steel sheet over time in the steel sheet manufacturing method of the first embodiment (when retention treatment is not performed). FIG. 3(b) shows the change in surface temperature of a slab (steel slab) or a steel sheet over time in the steel sheet manufacturing method of the second embodiment (when retention treatment is performed).
[0068] First Embodiment In the manufacturing method of the first embodiment of the steel sheet of the present invention, as shown in FIG. 3(a), a steel slab having the above-mentioned composition is hot-rolled and cold-rolled, and then the obtained cold-rolled steel sheet is subjected to the following process: (A c3After annealing at an annealing temperature of 200°C or higher and (Ms point (°C) -15°C) or lower and 900°C or lower, the material is cooled from the annealing temperature to a temperature T1 of 200°C or higher and (Ms point (°C) -30°C) or lower at an average cooling rate CR1: 3°C / s or higher and 100°C / s or lower, and heated from temperature T1 to a temperature T2 of 300°C or higher and 450°C or lower at an average heating rate of 2°C / s or higher, and heated from temperature T2 to a temperature range of (T2 - 150°C) or higher (T2 - 30°C). Cool the material at an average cooling rate CR2 of 0.5°C / s or more in the temperature range from temperature T3 to a temperature T4 of 150°C or more and 350°C or less and temperature T3 or less at an average cooling rate CR3 of 0.1°C / s or more, hold the material in the temperature range of 150°C or more and 350°C or less and temperature T4 or less for 20 s or more and 1000 s or less, and cool the material to a temperature of 50°C or less at an average cooling rate CR4 of 1°C / s or more.
[0069] (Hot rolling process) The hot rolling may be performed according to a conventional method. For example, a steel slab having the above-mentioned predetermined component composition may be heated to a slab heating temperature of 1100°C or higher, with a soaking time of 20 minutes or longer, hot-rolled at a finish rolling delivery temperature of the Ar3 transformation point or higher, and coiled at a coiling temperature of 400°C or higher. The slab heating temperature may be 1300°C or less. The soaking time may be 300 min or less. The finish rolling delivery temperature may be Ar3 transformation point + 200°C or less. The coiling temperature may be 720°C or less. The coiling temperature is preferably controlled from the viewpoint of suppressing thickness fluctuation and stably ensuring high strength. Specifically, the coiling temperature is preferably 430° C. or higher. Also, the coiling temperature is preferably 530° C. or lower.
[0070] (Cold rolling process) The cold rolling may be performed, for example, at a rolling ratio (cumulative rolling ratio) of 30% or more. The rolling ratio may be 85% or less. It is preferable to control the rolling ratio from the viewpoint of stably securing high strength and reducing anisotropy. Specifically, the rolling ratio is preferably 35% or more. When the rolling load is high, softening annealing can be performed at 450°C or more and 730°C or less in a CAL (continuous annealing line) or BAF (box annealing furnace).
[0071] (Annealing process) A steel slab having a predetermined composition is hot-rolled and cold-rolled, and then annealed under the following conditions. The annealing equipment is not particularly limited, but it is preferable to use a continuous annealing line (CAL) or a continuous hot-dip galvanizing line (CGL) from the viewpoints of productivity and ensuring the desired heating and cooling rates.
[0072] [Annealing process: Annealing temperature: (A c3 Temperature (℃) -15℃) or higher and lower than 900℃] In order to ensure a specified area fraction of tempered martensite and / or bainite and a specified area fraction of retained austenite, the annealing temperature is A c3 The annealing temperature (℃) is set to -15℃ or more and 900℃ or less. In order to make the ferrite content 15% or less, it is preferable to adjust the annealing temperature so as to achieve austenite single phase region annealing. The annealing temperature is preferably adjusted to A c3 Temperature is above. The annealing temperature is preferably A c3 Temperature (℃) + 15℃ or higher. On the other hand, if the annealing temperature exceeds 900°C, the austenite grain size becomes excessively large, and the diffusion distance of C atoms required to obtain the retained austenite with the desired carbon concentration becomes long, resulting in a decrease in ductility. Therefore, the annealing temperature is set to 900°C or less. The annealing temperature is preferably 880°C or less. In addition, A c3 The temperature can be determined by measuring the volume change when a cylindrical test piece (diameter 3 mm x height 10 mm) is heated from room temperature (25°C) to the austenite single phase region using a Formaster testing machine.
[0073] [First cooling treatment step: Cooling from the annealing temperature to a temperature T1 that is 200°C or higher and (martensitic transformation start temperature Ms point (°C) -30°C) or lower at an average cooling rate CR1: 3°C / s or higher and 100°C / s or lower] After the above annealing treatment, it is necessary to cool quickly in order to obtain a predetermined area ratio of tempered martensite and / or bainite. If the average cooling rate CR1 in the temperature range from the annealing temperature to a temperature T1 (cooling stop temperature T1) that is 200°C or higher and (martensitic transformation start temperature Ms point (°C) -30°C) or lower is less than 3°C / s, ferrite is generated during the cooling process, which reduces strength, stretch flangeability, and axial crush properties. Therefore, from the viewpoint of suppressing the generation of ferrite, the average cooling rate CR1 in the temperature range from the annealing temperature to a cooling stop temperature T1 that is 200°C or higher and (Ms point (°C) -30°C) or lower is set to 3°C / s or higher. The average cooling rate CR1 is preferably 5°C / s or higher, more preferably 8°C / s or higher. On the other hand, if the average cooling rate CR1 becomes too high, the sheet shape deteriorates, so the average cooling rate CR1 is set to 100° C. / s or less, and preferably 50° C. / s or less.
[0074] Moreover, in order to ensure a predetermined amount of retained austenite, the temperature T1 (cooling stop temperature T1) is set to 200°C or higher. The temperature T1 (cooling stop temperature T1) is preferably 220°C or higher, and more preferably 240°C or higher. If the cooling stop temperature T1 exceeds (Ms point (°C) - 30°C), a large amount of clumpy untransformed austenite remains, the amount of fresh martensite at the time of final cooling increases, and the stretch flangeability deteriorates. Therefore, the cooling stop temperature T1 is set to (Ms point (°C) - 30°C) or lower. The cooling stop temperature T1 is preferably (Ms point (°C) - 35°C) or lower.
[0075] The martensitic transformation start temperature Ms point (℃) was measured using a Formaster test machine. c3It can be determined by using a cylindrical test piece similar to that used for measuring the temperature, holding it at a prescribed annealing temperature, and then quenching it with helium gas, and measuring the change in volume.
[0076] Here, the average cooling rate CR1 is "(annealing temperature (cooling start temperature) (℃)-(Ms point (℃)-30℃) (cooling stop temperature (℃))) / (cooling time (seconds) from annealing temperature to (Ms point (℃)-30℃))".
[0077] [Heat treatment process: Heat from temperature T1 to temperature T2 between 300°C and 450°C at an average heating rate of 2°C / s or more] By heating in a short period of time from the above temperature T1 (cooling stop temperature T1: 200°C or higher and (martensitic transformation start temperature Ms point (°C) - 30°C or lower)) to a temperature T2 of 300°C or higher and 450°C or lower, carbide precipitation can be suppressed and, at the same time, carbon can be concentrated from the surrounding structure into the untransformed austenite, thereby ensuring high ductility. If the temperature T2 is less than 300°C, carbon is not sufficiently concentrated into the untransformed austenite, and further, the tempering of the martensite does not proceed sufficiently, resulting in an excessive increase in the strength of the tempered martensite, which is disadvantageous from the viewpoint of improving ductility and stretch flangeability. On the other hand, if the temperature T2 after heating exceeds 450°C, the untransformed austenite decomposes and the amount of massive fresh martensite increases, resulting in a decrease in ductility and stretch flangeability, and in addition, carbides are excessively precipitated, resulting in poor axial crushing properties. Therefore, the temperature T2 is set to 300°C or higher and 450°C or lower. The temperature T2 is preferably 330°C or higher, and more preferably 350°C or higher. The temperature T2 is preferably 420°C or lower, and more preferably 400°C or lower.
[0078] In addition, if the average heating rate from temperature T1 to temperature T2 of 300°C or more and 450°C or less is slow, the amount of carbide precipitation increases, deteriorating the axial crushing properties, and the amount of carbon enrichment in the retained austenite decreases with the increase in carbide, leading to a decrease in ductility. For this reason, the average heating rate in the temperature range from temperature T1 (cooling stop temperature T1) to temperature T2 of 300°C or more and 450°C or less is set to 2°C / s or more. From the viewpoint of suppressing carbide precipitation, the average heating rate is preferably 5°C / s or more, and more preferably 10°C / s or more. The upper limit of the average heating rate is not particularly limited, but the average heating rate is preferably 50°C / s or less, and more preferably 30°C / s or less.
[0079] Here, the average heating rate is "temperature T2 (heating stop temperature) (°C) - temperature T1 (heating start temperature) (°C)) / (heating time from temperature T1 to temperature T2 (seconds)).
[0080] [Second cooling process: Cooling in the temperature range from temperature T2 to temperature T3 between (T2-150℃) and (T2-30℃) at an average cooling rate CR2 of 0.5℃ / s or more] [Third cooling process: cooling from temperature T3 to temperature T4, which is 150°C or higher and 350°C or lower and lower than temperature T3, at an average cooling rate CR3 of 0.1°C / s or higher] In the overaging treatment process after cooling is stopped (from the above-mentioned heat treatment process to the holding treatment process after the third cooling treatment process), fresh martensite becomes martensite through tempering, and this transformation causes precipitation of carbides and carbon distribution to untransformed austenite. The rate of carbide precipitation tends to slow down as the heating temperature after cooling is stopped decreases, so by quickly cooling to a temperature range where carbide precipitation can be suppressed at a certain cooling rate or higher, it is possible to suppress carbide precipitation and improve axial crush properties. On the other hand, as the heating temperature decreases after cooling is stopped, carbon concentration in the untransformed austenite and tempering of fresh martensite is inhibited, which may result in an excessive increase in strength and deterioration of ductility and stretch flangeability. In view of the above, in order to simultaneously obtain excellent axial crushing properties, ductility, and stretch flangeability by cooling to a specified temperature range to suppress carbide precipitation and promoting carbon concentration in untransformed austenite and tempering of fresh martensite, a second cooling treatment step under specific conditions is performed between the heat treatment step and the third cooling treatment step. Specifically, in order to obtain the above-mentioned effects, the temperature T3 (cooling stop temperature T3) in the second cooling treatment step is set to be equal to or higher than (T2-150°C) and equal to or lower than (T2-30°C). The temperature T3 is preferably equal to or higher than (T2-120°C), and more preferably equal to or higher than (T2-100°C). The temperature T3 is preferably equal to or lower than (T2-50°C), and more preferably equal to or lower than (T2-70°C).
[0081] The average cooling rate CR2 is 0.5° C. / s or more, preferably 0.6° C. / s or more, and more preferably 0.7° C. / s. Although there is no particular upper limit, a high average cooling rate tends to delay carbon distribution to the retained austenite and tempering of fresh martensite, resulting in a decrease in ductility and stretch flangeability, and therefore the average cooling rate CR2 is preferably 5° C. / s or less.
[0082] Here, the average cooling rate CR2 is "(temperature T2 (°C) (cooling start temperature) - temperature T3 (°C) (cooling stop temperature)) / (cooling time from temperature T2 to temperature T3 (seconds))".
[0083] After cooling to a temperature T3 as the second cooling treatment, further cooling is performed as the third cooling treatment in order to suppress the precipitation of carbides while simultaneously promoting carbon distribution and improving the carbon concentration in and amount of retained austenite. At this time, if the cooling temperature is reduced, the carbon distribution rate decreases, and there is a concern that carbon will not be sufficiently concentrated in the untransformed austenite. On the other hand, as the cooling temperature increases and the average cooling rate decreases, carbides precipitate during cooling, deteriorating the axial crushing properties. Therefore, the temperature T4 is set to 150°C or higher and 350°C or lower. The temperature T4 is preferably 180°C or higher, and more preferably 200°C or higher. The temperature T4 is preferably 300°C or lower, and more preferably 250°C or lower.
[0084] The average cooling rate CR3 is 0.1° C. / s or more, preferably 0.2° C. / s or more, and more preferably 0.3° C. / s or more. Although there is no particular upper limit, from the viewpoint of sufficiently promoting carbon distribution to untransformed austenite, the average cooling rate CR3 is preferably equal to or less than the average cooling rate CR2 and equal to or less than 1° C. / s.
[0085] Here, the average cooling rate CR3 is "(temperature T3 (°C) (cooling start temperature) - temperature T4 (°C) (cooling stop temperature)) / (cooling time (seconds) from temperature T3 to temperature T4)".
[0086] [Holding process: Hold for 20s to 1000s at a temperature range of 150℃ to 350℃ and below T4] The holding temperature is set to be equal to or lower than the above temperature T4. If the holding temperature is less than 150°C, the tempering of fresh martensite does not proceed sufficiently, resulting in an excessive increase in strength, and furthermore, the amount of carbon enriched in the untransformed austenite decreases, which is disadvantageous from the standpoint of improving ductility and stretch flangeability. On the other hand, when the holding temperature exceeds 350°C, the amount of carbide precipitation increases, the axial collapse characteristics become inferior, and further, the precipitation of carbides inhibits carbon concentration in untransformed austenite, the amount of retained austenite decreases, and the ductility becomes inferior. For the above reasons, the holding temperature is set to 150° C. or higher and 350° C. or lower, and is set to temperature T4 or lower. The holding temperature is preferably 180° C. or higher, and more preferably 200° C. or higher. The holding temperature is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0087] Moreover, by increasing the holding time, the amount of carbon enriched in the untransformed austenite can be increased, and the retained austenite can be stabilized, making it possible to improve ductility. On the other hand, by shortening the holding time, the amount of carbide precipitation tends to decrease, improving the axial crushing properties. For the above reasons, the holding time is set to 20 s or more and 1000 s or less. The holding time is preferably 100 s or more, and more preferably 200 s or more. The holding time is preferably 700 s or less, and more preferably 500 s or less.
[0088] In addition, after the first cooling treatment step (after cooling at an average cooling rate CR1: 3°C / s or more and 100°C / s or less), that is, before or after any of the steps from the heating treatment step from temperature T1 to temperature T2 described above to the holding treatment step of holding at 150°C or more and 350°C or less, or during any of the steps, it is possible to perform hot-dip galvanizing treatment or further alloying treatment to form a zinc-plated layer on the steel sheet surface. In this case, it is preferable to immerse the steel sheet in a zinc-plating bath at 440°C to 500°C, perform hot-dip galvanizing treatment, and then adjust the coating weight by gas wiping or the like. For hot-dip galvanizing, it is preferable to use a zinc-plating bath having an Al content of 0.10 mass% to 0.22 mass%. In addition, after the hot-dip galvanizing treatment, a zinc-plating alloying treatment can be performed. When performing zinc-plating alloying treatment, it is preferable to perform it in a temperature range of 470°C to 590°C, and heating up to this temperature range does not impair the effects of the present invention, so it may be performed.
[0089] [Fourth cooling process: Cool to a temperature of 50°C or less at an average cooling rate of CR4:1°C / s or more] Thereafter, the steel sheet is cooled at an average cooling rate of CR4:1°C / s or more from the end temperature of the above-mentioned holding process (150°C or more and 350°C or less, and temperature T4 or less) to a temperature of 50°C or less in order to prevent softening due to excessive tempering and a decrease in ductility due to carbide precipitation. The steel sheet can be subjected to skin pass rolling in order to stabilize press formability, such as adjusting the surface roughness and flattening the sheet shape, and to increase the yield strength. The skin pass elongation is preferably 0.1% or more and 0.5% or less. The sheet shape can also be flattened using a leveller. The average cooling rate CR4 from the above-mentioned holding end temperature to a temperature of 50° C. or less is 1° C. / s or more, and preferably 5° C. / s or more. In the present invention, there is no upper limit for the average cooling rate CR4, but from the viewpoint of production and from the viewpoint of suppressing transformation from retained austenite to fresh martensite, it is preferably 10° C. / s or less.
[0090] Here, the average cooling rate CR4 is "(temperature (cooling stop temperature)) between 150°C and 350°C and below temperature T4 (°C) (end of holding temperature (cooling start temperature)) -50°C)) / (cooling time (seconds) from the end of holding temperature to the cooling stop temperature)."
[0091] From the viewpoint of improving stretch flange formability, it is also possible to perform a low-temperature heat treatment at 100 to 300°C for 30 seconds to 10 days after the above heat treatment or after skin-pass rolling. This treatment causes hydrogen that has entered the steel sheet during tempering or annealing of martensite formed during final cooling or skin-pass rolling to be released from the steel sheet. The low-temperature heat treatment can reduce hydrogen to less than 0.1 ppm by mass.
[0092] It is also possible to apply electroplating. That is, after the above-mentioned fourth cooling treatment step (after cooling at an average cooling rate CR4: 1°C / s or more), the steel sheet may be subjected to electrogalvanizing treatment. After electroplating, it is preferable to apply the above-mentioned low-temperature heat treatment from the viewpoint of reducing hydrogen in the steel.
[0093] Second Embodiment In the manufacturing method of the second embodiment of the steel sheet of the present invention, as shown in FIG. 3(b), a steel slab having the above-mentioned composition is hot-rolled and cold-rolled, and then the obtained cold-rolled steel sheet is subjected to the following process: (A c3 After annealing at an annealing temperature of 900°C or higher (Ms point (°C) -15°C), the material is cooled from the annealing temperature to 500°C at an average cooling rate of CR5: 5°C / s or higher and 100°C / s or lower (first cooling process before dwell treatment), and then cooled for 10 s to 60 s in the temperature range from 500°C to a dwell stop temperature T5 of 320°C or higher at an average cooling rate of CR6: 10°C / s or lower (dwell treatment), and then cooled for 10 s to 60 s in the temperature range from T5 to a dwell stop temperature T1 of 200°C or higher and 200°C or lower (Ms point (°C) -30°C) at an average cooling rate of CR7: 3°C / s or higher and 100°C / s or lower (second cooling process after dwell treatment). 1) Cooling treatment: Heat from temperature T1 to temperature T2 of 300°C or more and 450°C or less at an average heating rate of 2°C / s or more, cool from temperature T2 to temperature T3 of (T2-150°C) or more and (T2-30°C) or less at an average cooling rate CR2: 0.5°C / s or more, cool from temperature T3 to temperature T4 of 150°C or more and 350°C or less and temperature T3 or less at an average cooling rate CR3: 0.1°C / s or more, hold in the temperature range of 150°C or more and 350°C or less and temperature T4 or less for 20 s or more and 1000 s or less, and cool to a temperature of 50°C or less at an average cooling rate CR4: 1°C / s or more.
[0094] In the second embodiment, the hot rolling, cold rolling, and annealing treatment can be performed under the same conditions as in the first embodiment. In the second embodiment, the treatment in the first cooling treatment step in the first embodiment is a first cooling treatment before the retention treatment, a retention treatment, and a first cooling treatment after the retention treatment. In addition, in the second embodiment, the heating treatment, the second cooling treatment, the third cooling treatment, the holding treatment, and the fourth cooling treatment after the retention treatment and the first cooling treatment can be carried out under the same conditions as the heating treatment, the second cooling treatment, the third cooling treatment, the holding treatment, and the fourth cooling treatment in the first embodiment, respectively. In addition, in the second embodiment, the hot-dip galvanizing process can be performed under the same conditions as in the first embodiment, except that, whereas in the first embodiment, it is performed after the first cooling treatment step (after cooling at an average cooling rate CR1: 3°C / s or more and 100°C / s or less), in the second embodiment, it is performed after the first cooling treatment step after the retention treatment (after cooling at an average cooling rate CR7: 3°C / s or more and 100°C / s or less). In the second embodiment, other conditions including the low-temperature heat treatment after the total heat treatment and the conditions for the electroplating treatment can be the same as those in the first embodiment. In the present embodiment, the first cooling process before the retention process, the retention process, and the first cooling process after the retention process will be mainly described below.
[0095] [First cooling process before retention treatment: Cooling from the annealing temperature to 500°C at an average cooling rate of CR5: 5°C / s to 100°C / s] [Dwell treatment: Dwell for 10 to 60 seconds at an average cooling rate of CR6: 10℃ / s or less in the temperature range from 500℃ to the dwell stop temperature T5, which is above the Ms point (℃) and above 320℃] By performing a retention treatment during cooling, a larger amount of bainite can be obtained in terms of area ratio, carbon is concentrated from the bainite to the untransformed austenite, and the retained austenite is stabilized, thereby obtaining a steel sheet with better ductility. Therefore, from the viewpoint of high ductility, it is desirable to perform a retention treatment during cooling.
[0096] When holding treatment is performed during cooling, the steel is first cooled from the annealing temperature to 500°C at an average cooling rate CR5 of 5°C / s to 100°C / s. If the average cooling rate CR5 is lower than 5°C / s, a large amount of ferrite is generated, resulting in a decrease in strength and a decrease in λ. The average cooling rate CR5 is preferably 8°C / s or more. On the other hand, if the average cooling rate CR5 is too high, the sheet shape deteriorates, so the average cooling rate CR5 is 100° C. / s or less, preferably 50° C. / s or less, and more preferably less than 30° C. / s.
[0097] Here, the average cooling rate CR5 is "(annealing temperature (cooling start temperature) (°C)-500°C (cooling stop temperature)) / cooling time from the annealing temperature to 500°C (seconds)".
[0098] Next, by retaining the material in the temperature range from 500°C to a retention stop temperature T5 that is equal to or higher than the martensitic transformation start temperature Ms point (°C) and equal to or higher than 320°C for 10 to 60 seconds at an average cooling rate of CR6: 10°C / s or less, it is possible to form bainite, and adjacent to it, retained austenite with a high carbon concentration can be formed. If the temperature range is below the Ms point (°C), martensite forms first, and the bainite transformation progresses excessively due to the swing back phenomenon, resulting in reduced strength and stretch flangeability. On the other hand, when the temperature range exceeds 500°C, the driving force of the bainite transformation decreases, and the amount of bainite transformation decreases. In addition, when the temperature range is less than 320°C, lower bainite is mainly generated, but from the viewpoint of improving ductility and VDA bending properties, upper bainite without carbide precipitation is advantageous from the viewpoint of suppressing carbon-enriched carbides in untransformed γ and deterioration of axial crush properties due to carbide precipitation. Therefore, the retention stop temperature T5 is set to 320°C or higher. From the above, the temperature range is set to be equal to or higher than the Ms point (°C) and equal to or higher than 320°C and equal to or lower than 500°C. The temperature range is preferably equal to or higher than 350°C, more preferably equal to or higher than 380°C. The temperature range is preferably equal to or lower than 480°C, more preferably equal to or lower than 460°C.
[0099] If the average cooling rate CR6 exceeds 10°C / s, the amount of bainite transformation decreases. Therefore, the average cooling rate CR6 is set to 10°C / s or less. Furthermore, if the residence time is less than 10 s, the desired amount of bainite cannot be obtained, and if it exceeds 60 s, C concentration from bainite to the blocky untransformed austenite progresses, leading to an increase in the amount of remaining blocky structure. Therefore, the residence time is set to 10 s or more and 60 s or less. From the viewpoint of ensuring bainite and retained austenite, the residence time is preferably 20 s or more. Furthermore, from the viewpoint of improving stretch flangeability by reducing blocky structure, the residence time is preferably 50 s or less.
[0100] Here, the average cooling rate CR6 is "(500°C (retention start temperature) (°C) - (retention end temperature (°C) above the Ms point (°C) and above 320°C))) / (retention time (seconds) from the retention start temperature to the retention end temperature)".
[0101] [First cooling process after dwell treatment: Cooling in the range from the dwell stop temperature T5 to a temperature T1 that is 200°C or higher and (martensitic transformation start temperature Ms point (°C) -30°C) or lower at an average cooling rate CR7: 3°C / s or higher and 100°C / s or lower] After the above-mentioned holding treatment, it is necessary to cool quickly in order to obtain a predetermined area ratio of tempered martensite and / or bainite. If the average cooling rate CR7 in the temperature range from the holding stop temperature T5 to the temperature T1 (cooling stop temperature T1) which is 200°C or higher and (martensitic transformation start temperature Ms point (°C) -30°C) or lower is less than 3°C / s, ferrite is generated during the cooling process, which reduces the strength, stretch flangeability, and axial crush properties. Therefore, from the viewpoint of suppressing the generation of ferrite, the average cooling rate CR7 in the temperature range from the holding stop temperature T5 to the cooling stop temperature T1 which is 200°C or higher and (Ms point (°C) -30°C) or lower is set to 3°C / s or higher. The average cooling rate CR7 is preferably 5°C / s or higher, more preferably 8°C / s or higher. On the other hand, if the average cooling rate CR7 becomes too high, the sheet shape deteriorates, so the average cooling rate CR7 is set to 100° C. / s or less, and preferably 50° C. / s or less.
[0102] Moreover, in order to ensure a predetermined amount of retained austenite, the temperature T1 (cooling stop temperature T1) is set to 200°C or higher. The temperature T1 (cooling stop temperature T1) is preferably 220°C or higher, and more preferably 240°C or higher. If the cooling stop temperature T1 exceeds (Ms point (°C) - 30°C), a large amount of clumpy untransformed austenite remains, the amount of fresh martensite at the time of final cooling increases, and stretch flangeability deteriorates. Therefore, the cooling stop temperature T1 is set to (Ms point (°C) - 30°C) or lower. The cooling stop temperature T1 is preferably (Ms point (°C) - 35°C) or lower.
[0103] Here, the average cooling rate CR7 is "(retention stop temperature T5 (cooling start temperature) (℃)-(Ms point (℃)-30℃) (cooling stop temperature (℃))) / (cooling time from retention stop temperature T5 to cooling stop temperature (seconds))".
[0104] Next, the member of the present invention and the method for producing the same will be described.
[0105] The member of the present invention is obtained by subjecting the steel plate of the present invention to at least one of forming and joining. Also, the method for producing the member of the present invention includes a step of subjecting the steel plate of the present invention to at least one of forming and joining to obtain the member.
[0106] The steel plate of the present invention has a tensile strength of 980 MPa or more, and has high ductility, excellent stretch flange formability, and excellent axial crushing properties. Therefore, the member obtained by using the steel plate of the present invention is also high in strength, and has high ductility, excellent stretch flange formability, and excellent axial crushing properties compared to conventional high-strength members. In addition, the use of the member of the present invention allows weight reduction. Therefore, the member of the present invention can be suitably used, for example, for vehicle body frame parts. The member of the present invention also includes a welded joint.
[0107] The forming process may be performed by a general processing method such as pressing, without any restrictions. The joining process may be performed by a general welding method such as spot welding or arc welding, riveting, or crimping, without any restrictions. EXAMPLES
[0108] Cold rolled steel sheets having the composition shown in Table 1 and a thickness of 1.4 mm were treated under the annealing conditions shown in Tables 2 and 3 to produce steel sheets according to the present invention and comparative steel sheets. The cold-rolled steel sheets were obtained by subjecting a steel slab having the chemical composition shown in Table 1 to hot rolling (heating temperature: 1250°C, soaking time: 60 min, finish rolling outlet temperature: 1150°C, coiling temperature: 550°C) and cold rolling (rolling ratio (cumulative reduction): 50%). Table 2 shows the conditions when no dwell treatment is performed, and Table 3 shows the conditions when dwell treatment is performed. Note that some steel sheets (cold-rolled steel sheets: CR) were subjected to hot-dip galvanizing treatment in any step from heating at temperature T1 to holding at 150°C or less and 350°C or less to produce hot-dip galvanized steel sheets (GI). Here, the steel sheet was immersed in a zinc plating bath at 440°C to 500°C to carry out hot-dip galvanizing, and then the coating weight was adjusted by gas wiping or the like. A zinc plating bath with an Al content of 0.10% to 0.22% was used for the hot-dip galvanizing. Furthermore, some of the hot-dip galvanized steel sheets were subjected to an alloying treatment after the above hot-dip galvanizing treatment to produce alloyed hot-dip galvanized steel sheets (GA). Here, the alloying treatment was carried out in a temperature range of 460°C to 590°C. Furthermore, some of the steel sheets (cold-rolled steel sheets: CR) were subjected to electroplating to produce electrogalvanized steel sheets (EG).
[0109] [Table 1]
[0110] [Table 2]
[0111] [Table 3]
[0112] The steel structure was measured by the method described above. The measurement results are shown in Tables 4 and 5. Table 4 shows the conditions without holding treatment, and Table 5 shows the conditions with holding treatment.
[0113] (tensile strength, ductility) JIS No. 5 tensile test pieces and hole expansion test pieces were taken from the obtained steel sheets, and tensile tests (based on JIS Z2241 (2011)) were carried out. The tensile strength TS and total elongation T-El are shown in Tables 4 and 5. Those with a tensile strength of 980 MPa or more were judged to have excellent strength. In addition, the total elongation T-El was determined to be excellent when it was 14.0% or more for TS less than 1180 MPa, 12.0% or more for TS 1180 MPa or more and less than 1320 MPa, and 10.0% or more for TS 1320 MPa or more.
[0114] (Stretch flangeability) The stretch flangeability was evaluated by a hole expansion test in accordance with the provisions of the Japan Iron and Steel Federation standard JFST1001. That is, after punching a sample of 100 mm x 100 mm square size using a punching tool with a punch diameter of 10 mm and a die diameter of 10.3 mm (clearance 13%), the hole was expanded using a conical punch with an apex angle of 60 degrees so that the burrs generated during the punching hole formation were on the outside until a crack penetrating the plate thickness occurred. In this case, d0: initial hole diameter (mm), d: hole diameter at the time of crack occurrence (mm), and the hole expansion ratio λ (%) was calculated as {(d-d0) / d0}×100. The hole expansion ratio λ is shown in Tables 4 and 5. Steel sheets having a λ of 45% or more were judged to have excellent stretch flangeability.
[0115] (Axial crushing properties) FIG. 4 is a diagram for explaining a method for calculating the VDA bending angle. As shown in Fig. 4, to evaluate the axial crushing properties, the VDA bending angle α was evaluated by a bending test (Verband der Automobilindustrie: VDA bending test) in accordance with the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry. The VDA bending test is a three-point plate bending test characterized by very closely spaced rolls 10 and a sharp punch 11. For the VDA bending test, a 60 mm × 60 mm square test piece was used, and the bending ridge direction was parallel to the rolling direction. The test piece was supported by rolls with a roll diameter D of 30 mm and a roll distance L (not shown) of (sheet thickness a0 × 2) + 0.5 mm, and pressed from above with a punch with a tip r (radius of curvature) of 0.4 mm at a stroke speed of 20 mm / min (in the figure, symbol 11A indicates the punch before pressing, and symbol 11B indicates the punch after pressing). In FIG. 4, for the sake of explanation, the test piece (steel plate X) is illustrated symmetrically around the indentation axis. A , X B ), only one side of the roll 10 is shown. The VDA bending angle α is the bending angle (°) calculated using the formulas (1) to (5) from the stroke S (mm) at the maximum load in the bending test, and can be used as an index of axial collapse properties. Steel plates with an α of 80° or more were judged to have excellent axial crushing properties.
[0116] c(mm)=D / 2+r+a0...(Formula 1)
[0117] p(mm)=D / 2+L / 2 (Equation 2)
[0118]
number
[0119]
number
[0120]
number
[0121] [Table 4]
[0122] [Table 5]
[0123] The examples of the present invention shown in Tables 4 and 5 are excellent in strength, ductility, stretch flangeability and axial crushing properties, whereas the comparative examples are inferior in any of these properties.
[0124] In addition, it was found that the components obtained by forming, joining, and further forming and joining the steel plates of the present invention have high strength, high ductility, excellent stretch flange formability, and excellent axial crushing properties, similar to the steel plates of the present invention, because the steel plates of the present invention have high strength, high ductility, excellent stretch flange formability, and excellent axial crushing properties. [Industrial Applicability]
[0125] The present invention makes it possible to manufacture a steel sheet which is excellent in ductility, stretch flangeability, and axial crushing properties and is used for components of automobiles and home appliances, and is particularly suitable for energy absorbing components of automobiles, and can be preferably applied to the press forming of these components. [Explanation of symbols]
[0126] F Ferrite TM Tempered martensite UB Upper bainite LB Lower bainite FM Fresh martensite RA Retained austenite α VDA bending angle 10 rolls D Roll diameter 11 Punch 11A Punch before pressing 11B Punch after pressing S Stroke r tip radius of curvature X A Steel plate before pressing X B Steel plate after pressing a0 plate thickness
Claims
1. In mass percent, C: 0.10% or more and 0.30% or less, Si: 0.5% or more and 2.0% or less, Mn: 1.5% or more and 3.0% or less, P: 0.10% or less, S: 0.020% or less, sol. Al: 1.00% or less, N: 0.015% or less The composition is composed of the remainder Fe and unavoidable impurities, In terms of area ratio, Ferrite: 15% or less, Tempered martensite: 30% or more and 80% or less, Bainite: 10% or more and 40% or less, Retained austenite: 5% or more, Fresh martensite: 10% or less The steel structure contains The average C concentration in the retained austenite is 0.60 mass% or more, A steel sheet in which the content of Fe element present as carbides in tempered martensite is 0.20 mass% or less on average in a region within 100 μm from the steel sheet surface in the sheet thickness direction.
2. The composition further includes, in mass%, Ti: 0.100% or less, Nb: 0.100% or less, V: 0.100% or less, B: 0.0050% or less, Cr: 1.000% or less, Cu: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.100% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, REM: 0.0050% or less The steel sheet according to claim 1, comprising at least one selected from the following:
3. The steel sheet according to claim 1 , which has a zinc plating layer on the surface of the steel sheet.
4. The steel sheet according to claim 2 , which has a zinc plating layer on the surface of the steel sheet.
5. A member made using the steel plate according to any one of claims 1 to 4.
6. A steel slab having the composition according to claim 1 or 2 is hot-rolled and cold-rolled, and then the resulting cold-rolled steel sheet is subjected to the following steps: (A c3 After performing annealing treatment at an annealing temperature of 900°C or higher (temperature (°C) -15°C), Cooling is performed at an average cooling rate CR1 of 3° C. / s or more and 100° C. / s or less in the range from the annealing temperature to a temperature T1 of 200° C. or more and (Ms point (° C.)-30° C.) or less, Heating the temperature range from the temperature T1 to a temperature T2 of 300° C. or more and 450° C. or less at an average heating rate of 2° C. / s or more; Cooling the material at an average cooling rate CR2 of 0.5° C. / s or more in a temperature range from the temperature T2 to a temperature T3 of (T2-150° C.) or more and (T2-30° C.) or less; Cooling from the temperature T3 to a temperature T4 in a temperature range of 150° C. or more and 350° C. or less and equal to or less than the temperature T3 at an average cooling rate CR3: 0.1° C. / s or more; Hold the temperature in the range of 150° C. or more and 350° C. or less and the temperature T4 or less for 20 s or more and 1000 s or less, Cooling to a temperature of 50°C or less at an average cooling rate of CR4: 1°C / s or more; A method for producing a steel plate having a steel structure containing, in terms of area ratio, ferrite: 15% or less, tempered martensite: 30% or more and 80% or less, bainite: 10% or more and 40% or less, retained austenite: 5% or more, and fresh martensite: 10% or less, wherein an average C concentration in the retained austenite is 0.60 mass% or more, and the content of Fe element present as carbides in the tempered martensite is 0.20 mass% or less on average in a region within 100 μm from the steel plate surface in the plate thickness direction.
7. A steel slab having the composition according to claim 1 or 2 is hot-rolled and cold-rolled, and then the resulting cold-rolled steel sheet is subjected to the following steps: (A c3 After performing annealing treatment at an annealing temperature of 900°C or higher (temperature (°C) -15°C), Cooling the steel sheet in the temperature range from the annealing temperature to 500° C. at an average cooling rate CR5: 5° C. / s or more and 100° C. / s or less; The temperature range is from 500° C. to a retention stop temperature T5 that is equal to or higher than the Ms point (° C.) and equal to or higher than 320° C., and the retention time is 10 s to 60 s at an average cooling rate CR6 of 10° C. / s or less. Cooling is performed at an average cooling rate CR7 of 3° C. / s or more and 100° C. / s or less in the temperature range from the retention end temperature T5 to a temperature T1 of 200° C. or more and (Ms point (° C.)-30° C.) or less, Heating the temperature range from the temperature T1 to a temperature T2 of 300° C. or more and 450° C. or less at an average heating rate of 2° C. / s or more; Cooling the material at an average cooling rate CR2 of 0.5° C. / s or more in a temperature range from the temperature T2 to a temperature T3 of (T2-150° C.) or more and (T2-30° C.) or less; Cooling from the temperature T3 to a temperature T4 in a temperature range of 150° C. or more and 350° C. or less and equal to or less than the temperature T3 at an average cooling rate CR3: 0.1° C. / s or more; Hold the temperature in the range of 150° C. or more and 350° C. or less and the temperature T4 or less for 20 s or more and 1000 s or less, Cooling to a temperature of 50°C or less at an average cooling rate of CR4: 1°C / s or more; A method for producing a steel plate having a steel structure containing, in terms of area ratio, ferrite: 15% or less, tempered martensite: 30% or more and 80% or less, bainite: 10% or more and 40% or less, retained austenite: 5% or more, and fresh martensite: 10% or less, wherein an average C concentration in the retained austenite is 0.60 mass% or more, and the content of Fe element present as carbides in the tempered martensite is 0.20 mass% or less on average in a region within 100 μm from the steel plate surface in the plate thickness direction.
8. The method for producing a steel sheet according to claim 6, wherein the steel sheet is subjected to a hot-dip galvanizing treatment or a hot-dip galvannealing treatment after cooling at the average cooling rate CR1: 3°C / s or more and 100°C / s or less.
9. The method for producing a steel sheet according to claim 7, wherein the steel sheet is subjected to a hot-dip galvanizing treatment or a hot-dip galvannealing treatment after cooling at the average cooling rate CR7: 3°C / s or more and 100°C / s or less.
10. The method for producing a steel sheet according to claim 6, wherein the steel sheet is subjected to an electrolytic galvanizing treatment after cooling at the average cooling rate CR4: 1°C / s or more.
11. The method for producing a steel sheet according to claim 7, wherein the steel sheet is subjected to an electrolytic galvanizing treatment after cooling at the average cooling rate CR4: 1°C / s or more.
12. A method for manufacturing a component, comprising a step of subjecting the steel plate according to any one of claims 1 to 4 to at least one of forming and joining to form a component.
Citation Information
Patent Citations
High strength hot dip galvanized steel sheet and high strength hot dip alloyed galvanized steel sheet having excellent formability and hole expandability, method for producing high strength hot dip galvanized steel sheet and method for producing high strength hot dip alloyed galvanized steel sheet
JP2007211280A
High strength steel and manufacturing method
JP2017507241A
Method for producing high strength steel plate with improved ductility and formability and resulting steel plate
JP2019505691A
Steel sheet and manufacturing method therefor
WO2019186997A1
Steel sheet, member, method for producing said steel sheet, and method for producing said member
WO2022004817A1